The influence of teacher’s language impoliteness in triggering students’ bullying behavior - Mantasiah R; Yusri Yusri; Hasmawati Hasmawati; Nur Fadhilah Umar (Journal of Educational Science and Technology (EST), 2020)
The purpose of this study is to examine the influence of teacher’s language impoliteness in triggering students’ bullying behavior. The participants are the primary school students in Makassar by using purposive sampling approach. The participants are students who have bullying cases as a perpetrator in the last one month.  Observation, in-depth interview, and questionnaire are used to collect the data. Data Analysis technique employed was simple linear regression analysis. This study shows that impolite language uttered by the teacher influences students’ bullying behaviors. Students who are used to hearing these impolite utterances from their teachers tend to commit bullying behavior verbally at schools since they tend to consider this behavior as an acceptable behavior.